Complete mitogenome of the giant panda tick Haemaphysalis longicornis (Ixodida: Ixodidae) and its phylogenetic implications. Issue 3 (2nd July 2020) - Wang, Lidan; Zhou, Xuan; Deng, Linhua; Liu, Yunjian; Li, Yingxin; Chen, Yijun; Huang, Shan; Li, Guo; Huang, Yan; Zhang, Hemin; Wang, Chengdong; Li, Desheng; et al.
Abstract: Haemaphysalis longicornis (Ixodida: Ixodidae) is a common blood-feeding ectoparasite of the giant panda and poses significant health burden to wild and captive populations. In the present study, the complete mitogenome of the giant panda tick H. longicornis was sequenced using Illumina sequencing technology. The entire mitogenome was 14, 706 bp in length and encoded 37 genes including 13 protein-coding genes, 22 transfer RNAs and two ribosomal RNAs. Phylogeny showed that four isolates of H. longicornis, regardless of host origins or locations, clustered together and had a closer relationship with Haemaphysalis hystricis than other Haemaphysalis species among the subfamily Haemaphysalinae of Ixodidae. The cumulative mitochondrial DNA resources provide insights into genetic and phylogenetic studies of Haemaphysalis ticks.